Interrelations of risky behavior and sensation seeking in the behaviour of students - Bulotaitė, Laima; Zamalijeva, Olga (Psichologija, 2017)
Extraversion, psychoticism and positive/negative affectivity were found to be positively correlated to alcohol and drug use (Wicki, Kuntsche, & Gmel, 2010). Sensation seeking, as a personality variable that describes an individual‘s tendency to seek out for novelties and exiting stimuli, also can have impact on alcohol, drugs use and other types of risky behaviour (Hansen & Breivik, 2011; Negreiros, 2006; Zuckerman, 1979). The purpose of our study was to find out how much risky behaviour is common among university students and to reveal interrelations between risky behaviour and sensation seeking. 664 students from eight universities in Lithuania have been interviewed. The average age of students surveyed – 20,4 years (SD = 2,21), 76% of them represented women, 24% – men. We used a specially designed questionnaire to detect 12 types of risky behaviours: drug use, frequent alcohol use, binge drinking, smoking, driving under the influence of alcohol, riding with a drunk driver, not using seat belts, SMS writing while driving, extreme sports, suicidal thoughts, unprotected sexual intercourse and ≥2 sex partners during a one year period. The Sensation Seeking Scale, Form V (SSS-V, Zuckerman, 2007), was used. Only 5.2% of students are not involved in any risky behaviour. The most prevalent risky behaviour among students – excessive alcohol consumption (binge drinking). 67.3% of students declared such behaviour (over 6 standard drinks in one occasion). 50.8% admitted that they drove under the influence of alcohol. About one-third of students engage in such risky behaviour, such as smoking, frequent alcohol consumption, drug use, extreme sports, unsafe sex or texting while driving a car. Student men are more likely to exhibit risk behaviour than women: namely, the excessive use of alcohol, trying drugs, driving under the influence of alcohol, texting while driving, cultivating extreme sports and having more than 2 sexual partners during the last 12 months. The results revealed strong correlations between different types of risky behaviour in students. 11.3% of students engaged in a single type of risky behaviour, 49% – 2–4 types, 34.5% – 5 and more types of risky behaviour. Our results revealed that sensation seeking is a good predictor of the number of risky behaviours one might take part in – higher scores of the sensation seeking scale predict more types of student risky behaviour. In conclusion, it could be stated that sensation seeking is a personal variable, which gives up a lot information about behaviour in young people and could be used not only as a predictor of numbers of risky behaviour, but as a predictor of such types of risky behaviour, as drug use and extreme sports. The evaluation of sensation seeking in students allows us to choose the appropriate methods of prevention and early intervention of risky behaviour.